Basophil activation test for inhalant allergens in pediatric patients with allergic rhinitis - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; ÖĞÜLÜR, İSMAİL; BARIŞ, SAFA (ELSEVIER IRELAND LTD, 2017)
Objective: Flow cytometric quantification of in vitro basophil activation can be quite performant and reliable tool to measure IgE-dependent allergen-specific responses in allergic patients. Current study aimed to evaluate the clinical relevance of basophil activation test (BAT) for the diagnosis of pediatric grass pollen and house dust mite (HDM) allergies. Methods: Forty-seven patients suffering from allergic rhinitis with HDM and grass pollen co sensitization with clinical history of allergic rhinitis and/or asthma and 15 non-allergic healthy subjects were enrolled. BAT was determined by flow cytometry upon double staining with anti-IgE/anti-CD63 mAb. Results: Regarding HDM with cut-off point greater than 12.5% for CD63(+) basophils sensitivity and specificity of the BAT were 90% and 73%, with positive predictive value (PPV) and negative predictive value (NPV) as 0.70 and 0.91, respectively. The analysis of concordance of being either allergic or healthy in comparison to BAT results for HDM revealed a substantial concordance (K index = 0.61, p < 0.001). Grass pollen with cut-off point greater than 11%, BAT attained a sensitivity, specificity, PPV, and NPV of 96%, 93%, 0.98, and 0.88, respectively. The analysis of concordance of being either allergic or healthy in comparison to BAT results for grass pollen revealed an almost perfect concordance (K index = 0.87, p < 0.001). Conclusion: Our findings concluded that BAT is reliable technique in the diagnosis of sensitization to grass pollen and HDM. The sensitivity of BAT in pollen allergic children was found to be remarkably higher in our cohort compared to other studies. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Basophil activation test; CD63; Flow cytometer; Grass pollen; House dust mite; Sensitivity; IMMUNOGLOBULIN-E; POLLEN ALLERGY; FLOW-CYTOMETRY; RELEASE TESTS; GRASS-POLLEN; EXPRESSION; DIAGNOSIS; PERSPECTIVES; SENSITIVITY; ASTHMA